Atroposelective Synthesis of Biaryl N‐Oxides via Cu‐Catalyzed De Novo Heteroaromatic N‐Oxide Ring Formation - Ke Ma; Ting Qi; Lei Hu; Chen Chen; Wan Wang; Jun‐Long Li; Cheng Peng; Gu Zhan; Bo Han (Advanced Science)
Abstract Heteroaromatic N‐oxides, renowned for their highly polar N─O bond and robust structure, exhibit significant bioactivities and have played a pivotal role in various drug development projects since the discovery of Minoxidil. Moreover, heteroaromatic N‐oxides, featuring axially chiral biaryl frameworks, are indispensable as Lewis base catalysts and ligands in organic synthesis. Despite their importance, synthesizing these chiral compounds is challenging, necessitating chiral starting materials or resolution processes. Catalytic strategies rely on the functionalization of heteroaromatic N‐oxide compounds, leading to products with a relatively limited skeletal diversity. This study introduces a Cu‐catalyzed atroposelective method for synthesizing biaryl N‐oxides via de novo heteroaromatic N‐oxide ring formation. This mild and efficient approach achieves excellent stereoselectivities (up to 99:1 er), enabling the production of a wide array of N‐oxides with novel heteroaromatic scaffolds. The axially chiral N‐oxide product 3f demonstrates high stereoselectivity and recyclability as a Lewis base catalyst. Additionally, product 3e exhibits promising therapeutic efficacy against triple‐negative breast cancer, with IC50 values of 4.8 and 5.2 µm in MDA‐MB‐231 and MDA‐MB‐468 cells, respectively. This research not only advances the synthesis of challenging chiral heteroaromatic N‐oxides but also encourages further exploration of N‐oxide entities in the discovery of bioactive small molecules.